- Konten Review Skincare di Akun Tiktok ‘Dokter Detektif’ Dalam Membentuk Minat Beli: - - Aninda Maghfiratun Navila; Ratih Pandu Mustikasari (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2026)
The beauty industry in Indonesia, especially the skincare sector, experiences significant growth every year. Increasingly fierce competition between brands encourages the emergence of various claims on products, including overclaim practices that can harm consumers. This phenomenon has given rise to a variety of educational content, one of which is the TikTok account ‘Doctor Detective’ which reviews skincare products based on laboratory test results. The purpose of this study was to determine the effect of exposure to skincare review content on TikTok @dokterdetektif on followers' buying interest. The theoretical basis used is the Stimulus-Organism-Response (SOR) theory. The research approach uses explanatory quantitative with survey methods collected from 100 sample respondents through questionnaires. The results of this study indicate that there is a positive and significant influence between exposure to skincare review content on TikTok @dokterdetektif (X) on purchase intention (Y). Every 1% increase in content exposure, buying interest will also increase by 0.735.